Pathogenesis and signaling pathways related to iodine-refractory differentiated thyroid cancer - Zhao, Simeng; Zhao, Yuejia; Zhao, Yongfu; Wang, Guangzhi (Frontiers in Endocrinology, 2024)
Thyroid cancer is the most common malignant neoplasm within the endocrine system and the field of head and neck surgery. Although the majority of thyroid cancers, more than 90%, are welldifferentiated thyroid carcinomas with a favourable prognosis, the escalating incidence of this disease has contributed to an increasing number of patients with a propensity for recurrent disease, rapid disease progression, and poor or no response to conventional treatments. These clinical challenges are commonly attributed to alterations in key thyroid oncogenes or signaling pathways, thereby initiating tumour cell dedifferentiation events, accompanied by reduced or virtually absent expression of the sodium/iodine symporter (NIS). As a result, the disease evolves into iodine-refractory differentiated thyroid cancer (RAIR-DTC), an entity that is insensitive to conventional radioiodine therapy. Despite being classified as a differentiated thyroid cancer, RAIR-DTC has an extremely poor clinical prognosis, with a 10-year survival rate of less than 10%. Therefore, it is of paramount importance to comprehensively elucidate the underlying pathogenesis of RAIR-DTC and provide specific targeted interventions. As the pathogenic mechanisms of RAIR-DTC remain elusive, here we aim to review recent advances in understanding the pathogenesis of RAIR-DTC and provide valuable insights for the development of future molecularly targeted therapeutic approaches.